Systemic view of learning scientific concepts: A description in terms of directed graph model. Issue 3 (7th October 2013) - Koponen, Ismo T.
<x xml:space="preserve">Abstract</x> This study suggests a systemic view on concept learning, in which concepts are seen as complex, dynamically evolving structures with robust and persistent patterns emerging from loosely connected elemental pieces. The model is represented in the form of a directed graph, and it explains many empirically identified features of learning paths, including: (1) the stability of learned concepts, (2) changes in concept attributions (ontological shift) as guided by theoretical knowledge, and (3) the evolution of concepts as driven by model competition with the accumulation of evidence. The results thus show applicability of the systemic view and the directed graph model. © 2013 Wiley Periodicals, Inc. Complexity 19: 27–37, 2014